2014
DOI: 10.1103/physrevb.89.205404
|View full text |Cite
|
Sign up to set email alerts
|

Phonon spectrum and electron-phonon coupling in zigzag graphene nanoribbons

Abstract: In this paper, we report a first-principles study of the lattice dynamics of small graphene nanoribbon with zigzag edges. Our investigation is based on spin polarized density functional calculations (DFT). Nesting properties in the electronic band structure are very different for nanoribbons with unpolarized, ferromagnetic, and antiferromagnetic configurations. As a result, the phonon spectrum and nesting related softening in phonon frequencies differ in these cases. The unpolarized and ferromagnetic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, various theoretical calculations demonstrate that the phononmediated superconductivity does not occur in the intrinsic graphene, due to the weak electron-phonon coupling constant [10], [11], [12]. This fact follows the case of graphite, where the induction of the superconducting phase is possible only via the chemical process know as intercalation [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, various theoretical calculations demonstrate that the phononmediated superconductivity does not occur in the intrinsic graphene, due to the weak electron-phonon coupling constant [10], [11], [12]. This fact follows the case of graphite, where the induction of the superconducting phase is possible only via the chemical process know as intercalation [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the one-atom-thick two-dimensional form of carbon, known as graphene [6], attracted exceptional attention in recent years, when comparing to the other carbon allotropes [7], [8], [9]. However, various theoretical calculations demonstrate that the phononmediated superconductivity does not occur in the intrinsic graphene, due to the weak electron-phonon coupling constant [10], [11], [12]. This fact follows the case of graphite, where the induction of the superconducting phase is possible only via the chemical process know as intercalation [13].…”
Section: Introductionmentioning
confidence: 99%
“…(II) For excitations of the leads a different picture emerges. The electron–phonon coupling constant, as calculated by Zhang et al, was found to be strong (λ = 0.14) in periodic 2-ZGNR and 4-ZGNR. The phonon lifetimes of the associated bath modes, , are thus in the picosecond regime, much faster than the dynamics of the switching process reported here.…”
Section: Resultsmentioning
confidence: 70%
“…The scaling factor is the thermal conductance quantum κ 0 (T ) = exist for an infinite width, i.e. for the two-dimensional graphene sheet [38,39,40]. Furthermore, comparing the APG with the ZPG structures, one can see larger differences in κ ph (T ) for the two nanopore sizes in the former case, which may develop from an enhanced deformation of the APG structures.…”
Section: Resultsmentioning
confidence: 99%
“…Finite width nanoribbons are quasi one-dimensional systems and there are four acoustic phonon branches: the outof plane mode (ZA), the in-plane transverse mode (TA), the in-plane longitudinal (LA) and a torsion branch, which does not exist for an infinite width, i.e. for the two-dimensional graphene sheet [38,39,40]. Furthermore, comparing the APG with the ZPG structures, one can see larger differences in κ ph (T ) for the two nanopore sizes in the former case, which may develop from an enhanced deformation of the APG structures.…”
Section: Resultsmentioning
confidence: 99%